(untitled) (Al-Qamar, 2021)
This study explores the phenomenon of beggary through the lens of Islamic teachings while highlighting practical and constructive approaches for its prevention. Beggary has become an increasingly visible social problem that not only disturbs public spaces but also erodes human dignity and weakens the moral and economic foundations of society. Islamic teachings place strong emphasis on self-reliance, lawful earning, and maintaining personal honor. The Qur’an and Sunnah discourage unnecessary or habitual begging, urging individuals instead to work, contribute to their communities, and uphold social harmony. The research examines the Islamic mechanisms that offer long-term solutions to poverty, such as zakat, sadaqah, waqf, and various forms of social support systems that help eliminate the root causes of beggary. These charitable institutions promote economic stability and ensure equitable distribution of resources within society. Moreover, the study stresses the importance of governmental policies, public awareness, and structured rehabilitation programs aimed at equipping beggars with the skills and opportunities necessary for a dignified livelihood. By combining classical Islamic principles with contemporary social strategies, this research presents a holistic framework for reducing beggary and fostering a more responsible, compassionate, and self-sufficient society.